Anaesthesia workload measurement devices: qualitative systematic review - Almghairbi, Dalal S.; Marufu, Takawira C.; Moppett, Iain K. (BMJ Publishing Group, 2018)
Background: Management of mental workload is a key aspect of safety in anaesthesia but there is no gold standard tool to assess mental workload, risking confusion in clinical and research use of such tools.